Impact of prenatally diagnosed congenital heart defects on outcomes and management. Issue 5 (11th May 2022) - Wong, Jennifer; Kohari, Katherine; Bahtiyar, Mert Ozan; Copel, Joshua
Abstract: Fetal echocardiogram aids in prenatal identification of neonates at high risk for congenital heart defects (CHD). Prenatal detection rates for CHD have increased with improved ultrasound technology, the use of the early fetal echocardiography, and standardization of the performance of the fetal echocardiogram. Accurate prenatal detection of CHD, particularly complex CHD, is an important contributor to improved survival rates for patients with CHD. Early detection allows for families to choose whether or not to continue with pregnancy, referral to pediatric cardiology specialists for patient education, and delivery planning. Better psychosocial supports are needed for families with CHD. Abstract : Accurate prenatal detection of CHD improves survival rates for patients with CHD, particularly complex CHD. Early detection also allows for families to choose whether or not to continue with pregnancy, referral to pediatric cardiology specialists for patient education, and delivery planning which may improve the family's sense of control.